Longevidade e psicomotricidade: ter ou ser um corpo que envelhece com qualidade de vida - Galvani, Cláudia (2015)
The study of aging and old age is essential to admit the reality of longevity and the increase in the elderly population. In this view emphasize the need to recognize the importance of the body, their histories and sociocultural characteristics. The Psychomotor in its interface with the Gerontology arises as generating area of competence of new knowledge about the elderly in a healthy condition of life. It is justifiable, therefore, this study conducted to investigate the views of older people on Aging, Longevity, body and different dimensions of Quality of Life in order to contribute in the structuring of educational policies with basement in the Psychomotor. This research is based on supporting a specific theoretical framework of the area of Social Gerontology, covering concepts related to aging, old age, citizenship, quality of life and psychomotor. The exploratory study and quantitative and qualitative approach includes field research conducted through interviews with 15 (fifteen) elderly goers Living Center for the Elderly - Calebe, participants of "psychomotor Workshops". Data collection occurred with the use of the WHOQOL-bref questionnaire and conducting with semi-structured interview based on a script and application of the procedures required by the ethical requirements. As collection and data analysis tools were used, from a quantitative point of view, the Student's T test. The results demonstrated the uniqueness and the subjectivity of the concept of quality of life and the positive impact of "psychomotor workshops" in daily life of the participants, as well as guiding new public policies in an intersectoral vision, covering the area of education, health and social